A plant based study of the feeding ecology of introduced herbivore game species in the Central Free State - Janecke, Beanelri Benene (University of the Free State, 2011)
Wag-‘n-Bietjie Private Nature Reserve is situated ±30 km north of Bloemfontein in the summer rainfall area. The northern part is 437 ha in size and represents a transition between grassland and riparian vegetation. Vegetation types present are grassland, open thickets, dense thicket, drainage lines of the Modder River, a wetland and disturbed area. Phenology (seasonal leaf carriage) of plants formed the basis of this study. Percentage leaves in each phenophase (Budding-, Immature-, Mature-, Yellow- and Dry leaves) was noted fortnightly for specific marked trees and shrubs representing each vegetation type. The deciduous nature of woody species influenced quality and quantity of browse available for herbivores. Consequently the nitrogen concentration in faeces (Nf) of four game species was determined to indicate their nutritional status through the different seasons. The rise and fall of Nf values corresponded to the seasonal increase and decrease of leaves (phenology pattern). Nf ranged during four years from 18 – 37 gN/kgDM for giraffe, 14 – 33 g/kg for kudu, 16 – 35 g/kg for eland and 17 – 28 g/kg for impala. Abovementioned minimum concentrations are close to, and in the case of kudu below known critical values where animals start to lose body condition. Nitrogen is the most limiting nutrient in the dry, cool season and is linked to protein percentage present in browse. Browse becomes a limited resource in the winter, therefore certain game species moved seasonally to different areas inside the private reserve in search of food. It was decided to supply feed in order to sustain animals and help them maintain body condition during the critical period that was established to be from July/August to middle October. The duration of feeding is important and it is recommended to start feeding from July at a low ration and then gradually increase feed towards the end of the critical period in correspondence with the declining browse and grass resources. Average monthly leaf carriage percentages were used to calculate browsing capacity per month in each vegetation type and in the study area as a whole. Browser units that could be sustained on browse resources within the 0 – 2 m stratum ranged from 1 – 6.7 BU between winter and summer due to the deciduousness of all woody plants present in the study area. This justifies in some way the provision of feed, or else the numbers of animals would need to be reduced to 1 BU which does not represent sustainable populations. Viable population numbers, economic value, diet and reproduction rates were used in determining the numbers of individual animals that can be stocked. Grazing capacity of the area differed according to annual rainfall and increased with higher rainfall. Consequently it needs to be recalculated annually. Habitat occupied by all 17 herbivore species was determined. Some species did not historically occur in the province. Most of them have adapted to the central Free State conditions over time, while others were introduced more recently. Inter-species competition for space and food resources proved to be high in the study area. A reduction in animal numbers has been recommended to limit competition. There is an ever increasing number of private game ranches in the province, >343 in August 2010, that will benefit from this research. Some general, operational guidelines have been presented that are applicable to the management of other game ranches in the province as well. When calculating individual animal numbers equivalent to carrying capacity values of other areas, the percentage grass and browse that herbivores include in their diet need to be adjusted to the specific area for accurate stocking densities.
Thesis (Ph.D. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2011
Keywords: Herbivores -- Ecology -- South Africa -- Free State; Grazing -- South Africa -- Orange Free State; Habitat (Ecology); Seasonal movements; Mixed feeders; Management plan; Leaf phenology; Impala; Eland; Kudu; Giraffe; Game ranch; Faecal nitrogen; Carrying capacity; Browsers